2008
DOI: 10.1002/elsc.200800016
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Release from a Natural Rock under Near‐natural Oxidizing Conditions

Abstract: 11The solubilization of arsenic (As) from an ore material (native Arsenic [As, trig.] with 12Lollingite [FeAs 2 , rh.]) was characterized in leaching tests lasting for ≤ 99 days. The 13 experiments were performed with materials of different particle sizes (≤ 2 mm), in different 14 waters and under test conditions relevant to As mobilization at near surface contaminated 15 sites. The impact of dolomite [CaMg(CO 3 ) 2 ], metallic iron (Fe 0 ), and pyrite (FeS 2 ) on As 16 release was accessed. Two different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…It is established that the most of these investigations have been based on to measure total arsenic from the various environmental samples (Rigol et al 2009;Noubactep et al 2008;Noubactep 2012;Igarashi et al 2008;Tabelin and Igarashi 2009). However, in the sequential extraction procedure (SEP) ammonium dihydrogen phosphate (NH 4 H 2 PO 4 ) has been used for arsenic leaching (Fedotov et al 2005;Lombi et al 2000) and finally total arsenic is measured without distinguishing arsenite and arsenate.…”
Section: Introductionmentioning
confidence: 99%
“…It is established that the most of these investigations have been based on to measure total arsenic from the various environmental samples (Rigol et al 2009;Noubactep et al 2008;Noubactep 2012;Igarashi et al 2008;Tabelin and Igarashi 2009). However, in the sequential extraction procedure (SEP) ammonium dihydrogen phosphate (NH 4 H 2 PO 4 ) has been used for arsenic leaching (Fedotov et al 2005;Lombi et al 2000) and finally total arsenic is measured without distinguishing arsenite and arsenate.…”
Section: Introductionmentioning
confidence: 99%
“…The results of leaching tests carried out on a VI rock sample and a CI rock sample, both with similar arsenic contents of about 30 mg/kg, show that the release of arsenic in steady state conditions is very small: the fractions of total bulk arsenic in the whole rock released from VI and CI samples are about 0.8% and 0.4%, respectively, after 168 h. The trends of release of the two samples are similar, as shown in Figure 10. The leaching tests were performed using deionized water as in other literature papers simulating water-rock or soil-water interactions [43][44][45]50,51] and also the effect of infiltration [52]. The use of real groundwater of the investigated area was not suitable, because its arsenic content (result of different factors including the natural rock-water interaction) would alter the study of the desorption/leaching behaviour we were investigating, as demonstrated by the results (not showed here) of preliminary tests performed for the choice of the experimental conditions.…”
Section: Rock Analyses and Leaching Testsmentioning
confidence: 99%
“…While the concept that lowering pH could enhance the dissolution of aquifer minerals and increase aqueous concentrations of contaminants in groundwater is reasonable, in the case of sulfides or other redox-sensitive minerals, redox conditions would be expected to have the greatest effect on their precipitation and dissolution behavior (Abdelouas et al 1999;Lee and Hering 2005;Rashid et al 2002;Sasaki et al 2010;Nickson et al 2000;Noubactep et al 2008;Smedley and Kinniburgh 2002;Edwards et al 2000). Thus, considering the influence of CO 2 intrusion rate on both pH and Eh and their coupled effects on the beneficial and deleterious reactions in the subsurface would provide a more complete scenario of what to expect within a particular environment.…”
Section: Importance Of Co 2 Intrusion Ratesmentioning
confidence: 99%
“…Such effects further indicate that gas composition could have significant implications for the mobility of As and other redox-sensitive contaminants (e.g., V, U, Se and Cr) in the subsurface, since their mobility is strongly influenced by speciation (Abdelouas et al 1999;Lee and Hering 2005;Rashid et al 2002;Sasaki et al 2010;Nickson et al 2000;Noubactep et al 2008;Smedley and Kinniburgh 2002). In cases where gas composition favors a shift from more to less mobile species (e.g., As(III) or Cr(VI) to As(V) and Cr(III), respectively), CO 2 intrusion could be considered beneficial, while in cases where the alternative shift is favored, then CO 2 intrusion would be deleterious.…”
Section: Importance Of Co-injected/co-transported Gasmentioning
confidence: 99%
See 1 more Smart Citation